Pooling Talent: Swimming's Greatest Teams - De George, Matthew (Rowman & Littlefield Publishers, 2014)
Swimming is primarily an individual endeavor, yet certain accomplishments, even by some of the most illustrious names in the sport, can only be fully appreciated when considered alongside the contributions of their teammates. After all, Michael Phelps would never have earned a record eight gold medals in the 2008 Olympics were it not for his teammates’ world record-setting efforts in the 400 freestyle relay. In Pooling Talent: Swimming’s Greatest Teams, Matthew De George highlights the top relay teams, squads, and programs in the history of competitive swimming. Each chapter describes in detail the history surrounding the team, the crucial races, and the key swimmers. Part I examines relay teams—such as the 1976 U.S. Women’s 400 Freestyle, the 2000 Australian Men’s Freestyle, and the 2004 U.S. Men’s Medley—showcasing how four opponents in the individual events can mesh seamlessly into a team. Part II explores the national squads, spanning from the 1924 U.S. Olympians to the 2001 World’s Australians, revealing the interplay between team and individual success. In Part III, the top developmental programs around the world are featured, including the 1930 Japanese Men’s program and the North Baltimore Aquatic Club. Together, the relay teams, squads, and programs provide constant motivation, pushing individuals to achieve much more than they ever could in isolation. Extensively researched and rich in detail, Pooling Talent takes a novel look at swimming accomplishments old and new, casting the accolades of individuals in a fresh light. Fans, coaches, athletes, and researchers alike will find this a unique and refreshing history of swimming’s greatest teams.